2020
DOI: 10.1155/2020/9478949
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed Genes in Different Types of Broiler Skeletal Muscle Fibers Using the RNA-seq Technique

Abstract: The difference in muscle fiber types is very important to the muscle development and meat quality of broilers. At present, the molecular regulation mechanisms of skeletal muscle fiber-type transformation in broilers are still unclear. In this study, differentially expressed genes between breast and leg muscles in broilers were analyzed using RNA-seq. A total of 767 DEGs were identified. Compared with leg muscle, there were 429 upregulated genes and 338 downregulated genes in breast muscle. Gene Ontolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The expression levels of PERK, IRE1 and ATF6 pathway-related proteins were detected by Western blotting. Notably, lncRNA-SUSAJ1 positively regulated the ER stress response, promoted the expression of IRE1, and promoted the phosphorylation of eIF2α, an important marker of PERK pathway activation [48]; however, it did not affect the ATF6 pathway. NF-κB is a protein complex that controls the transcription of various genes and participates in cellular responses to stress, free radicals, ROS, and cytokines; it also inhibits apoptosis [43].…”
Section: Discussionmentioning
confidence: 96%
“…The expression levels of PERK, IRE1 and ATF6 pathway-related proteins were detected by Western blotting. Notably, lncRNA-SUSAJ1 positively regulated the ER stress response, promoted the expression of IRE1, and promoted the phosphorylation of eIF2α, an important marker of PERK pathway activation [48]; however, it did not affect the ATF6 pathway. NF-κB is a protein complex that controls the transcription of various genes and participates in cellular responses to stress, free radicals, ROS, and cytokines; it also inhibits apoptosis [43].…”
Section: Discussionmentioning
confidence: 96%
“…An investigation of the development situation of other muscle parts is needed. As described by Wang et al (39), the muscle growth-related genes have different expression schedules in different tissues (legs and breast muscle). In brief, we concluded that in ovo delivery of DS or Met positively affects the development of breast muscle by regulating the expression of breast muscle growth-related genes during the early-life posthatching of goslings.…”
Section: Discussionmentioning
confidence: 98%
“…Chicken skeletal muscle satellite cells were those used in our prior studies ( Wang et al., 2020 ). After sterilizing 10-day-old breeding eggs with alcohol, they were placed on an egg tray, gently broken, and the shell was removed using tweezers.…”
Section: Methodsmentioning
confidence: 99%